2019
DOI: 10.1177/1060028019888853
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, Safety, and Economic Comparison of Inhaled Epoprostenol Brands, Flolan and Veletri, in Acute Respiratory Distress Syndrome

Abstract: Background: No previous studies exist examining 2 inhaled epoprostenol formulations in an acute respiratory distress syndrome (ARDS) patient population. Objective: The study aim was to evaluate a formulary conversion from inhaled Flolan to Veletri to determine the impact on effectiveness, safety, and cost in patients with ARDS. Methods: This was a single-center, retrospective, matched cohort observational study at a tertiary care academic medical center. Patients included were mechanically ventilated, adult pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 20 publications
(33 reference statements)
0
12
3
Order By: Relevance
“…Although there were only 11 patients that transitioned to iNO, there was a similar observed change in Pa o 2 /F io 2 . These results are different from what previous studies have shown when inhaled vasodilators have been used for refractory hypoxemia in ARDS unrelated to COVID-19 ( 8 , 9 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although there were only 11 patients that transitioned to iNO, there was a similar observed change in Pa o 2 /F io 2 . These results are different from what previous studies have shown when inhaled vasodilators have been used for refractory hypoxemia in ARDS unrelated to COVID-19 ( 8 , 9 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Several analyses comparing both agents have shown iEPO to be noninferior to iNO in patients with ARDS regarding safety, changes in oxygenation, and improvement in clinical outcomes, such as ventilator-free days ( 8 , 10 , 25 ). It is unclear if and how ARDS in patients with COVID-19 differs, but we saw less of an improvement in oxygenation metrics compared with previous studies ( 8 , 9 , 26 ). Our patients had significant differences at baseline, specifically decreased use of corticosteroids and increased use of neuromuscular blockade and prone-positioning, compared with previous studies evaluating ARDS unrelated to COVID-19 ( 9 , 26 ).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…It is effective in reducing pulmonary pressures and increasing oxygenation by improving V/Q matching, and has minimal adverse events (146)(147)(148)(149). More importantly, depending on the institution's contracted price, the use of iEPO is associated with significant savings, and there is no difference between Flolan and Veletri (150,151).…”
Section: Epoprostenolmentioning
confidence: 99%
“…Inhaled epoprostenol (iEPO), a naturally occurring prostaglandin that acts as vascular smooth muscle relaxant, has been utilized clinically for over two decades and has been shown to reduce pulmonary artery pressure [ 1 5 ] and improve oxygenation [ 3 12 ]. Despite its clinical significance, an optimal delivery strategy remains unknown.…”
Section: Introductionmentioning
confidence: 99%